Modeling of light extraction efficiency of scattering thin film using Mie scattering - Cheong, S.W.; Woon, K.L. (International Society for Optical Engineering, 2011)
Significant amount of emitted light from an organic light emitting diode (OLED) is trapped as a result of total internal reflection (TIR) on a glass–air interface. One of the strategies to increase the light extraction efficiency is using a scattering thin film. A model is built using the Monte Carlo ray tracing method to simulate Mie scattering. Almost 100% of light trapped by the TIR can be extracted if the radius of the spherical scatters, the refractive index ratio between the matrix and the scatter and the concentration of the scatter are optimized. The implication is important for a high efficiency OLED used in the next generation lighting source.